Front Metter SOCA Vol 15, No 3, September 2021 - September, Front Metter SOCA Vol 15, No 3, (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 15 No 3 (2021): Vol.15, No.3, 2021, 2021)
Front Metter SOCA Vol 15, No 3, September 2021